Βιβλιοκρισία του: T. C. LOUNGHIS,Byzantium in the Eastern Mediterranean: Safeguarding East Roman Identity (407 – 1204), Nicosia (Cyprus Research Centre. Texts and Studies in the History of Cyprus, LXIII) 2010 - COSENTINO, Salvatore (Byzantina Symmeikta, 2012)
Βιβλιοκρισία του: T. C. LOUNGHIS, Byzantium in the Eastern Mediterranean: Safeguarding East Roman Identity (407 – 1204), Nicosia 2010 (Cyprus Research Centre. Texts and Studies in the History of Cyprus, LXIII), pp. IX-XXXIV, 1-220, ISBN: 978-9963-0-8118-9.